(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the results of field experiments on salt leaching and water-saving irrigation technology for cotton in the heavily saline, heavy loam soils of the long-irrigated alluvial meadows of Bukhara region. The study evaluates salt balance, with results showing that salt content decreased by 3.3 t ha-1 in the second variant and by 7 t ha-1 in the third variant compared to the control.